2001
DOI: 10.1089/108076801753162762
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-Induced Changes of Secondary Messengers in Cultured Corneal Endothelial Cells

Abstract: The effect of endothelins on corneal endothelial cells is not well understood. We have investigated the effects of endothelin-1 (ET-1), endothelin-2 (ET-2) and endothelin-3 (ET-3) on bovine corneal endothelial cellular proliferation and the secondary messenger changes in cells in the presence of ET-1. It was found that the 3H-thymidine uptake was enhanced by ET-1 significantly, whereas ET-2 and ET-3 had no effect. ET-1 remarkably affects the increase of corneal endothelial cells on 3H-thymidine, 3H-leucine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Incorporation of thymidine into DNA has been used as an index of cell proliferation in HUVECs (Sobrevia et al 1996;Lau & Ma, 1996;Zanetti et al 2001;Bussolati et al 2001) and other endothelial cell types (Parenti et al 1998;Heller et al 1999;Grant et al 1999;Wu et al 2001;Kim et al 2001;Wang et al 2002;Spyridopoulus et al 2002). Thymidine incorporation was reduced in HUVECs incubated with 25 mM D-glucose for 24 h (Sobrevia et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporation of thymidine into DNA has been used as an index of cell proliferation in HUVECs (Sobrevia et al 1996;Lau & Ma, 1996;Zanetti et al 2001;Bussolati et al 2001) and other endothelial cell types (Parenti et al 1998;Heller et al 1999;Grant et al 1999;Wu et al 2001;Kim et al 2001;Wang et al 2002;Spyridopoulus et al 2002). Thymidine incorporation was reduced in HUVECs incubated with 25 mM D-glucose for 24 h (Sobrevia et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…cGMP, a second messenger for NO (Shaul, 2002), and cAMP are increased by high levels of D-glucose (Sobrevia et al 1996), and induce inhibition (Zanetti et al 2001;Wu et al 2001;Kim et al 2001) or stimulation (Grant et al 1999;Wu et al 2001) of endothelial cell proliferation. D-Glucose also activates protein kinase C, which is associated with longer term increases in NO production in HUVECs (Pan et al 1995;Montecinos et al 2000) and inhibition of endothelial cell proliferation (Wang et al 2002;Spyridopoulus et al 2002).…”
mentioning
confidence: 99%
“…17,18 The cultured corneal stromal cells were plated into 12-well plates for at least 24 hr to ensure attachment. Cultured cells were incubated with serumfree RPMI 1640 medium with various concentrations of latanoprost ranging from 10 −5 , 10 −6 , 10 −7 to 10 −8 M for 1.5 hr.…”
Section: H-thymidine H-leucine H-uridine and H-proline Uptakementioning
confidence: 99%
“…Previous work has found that corneal endothelium intracellular Ca 2ϩ can be increased through receptor-mediated pathways by histamine (5, 6), purinergic agonists (5, 30), bradykinin (5,40), and endothelin-1 (5,38). Adrenergic agonists decreased [Ca 2ϩ ] i (34).…”
Section: Discussionmentioning
confidence: 95%